Evaluating motor competence in children and youth: a narrative review - Silva, Ana Filipa (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Motor competence (MC) refers to the ability to execute a range of motor tasks, including the coordination and control necessary to perform everyday activities effectively. Interest in MC has grown over the past two decades, as reflected in an increasing number of publications on the topic. However, there is still no consensus on how to assess MC, with various test batteries available. A single test is insufficient for evaluating MC, as it encompasses a set of fundamental skills essential for daily life. These skills are typically categorised into fundamental movement skills, although discrepancies exist in their definitions. Some frameworks recognise two components – locomotor and manipulative skills – while others include a third component: stability skills. This review aims to analyse why, when and how MC should be assessed in children and adolescents. It was observed that MC assessments are essential at a young age, with physical education classes providing an ideal context for their implementation. Such assessments promote sports participation, aid in talent identification and highlight the positive correla-tion between MC and lifelong physical activity. Selecting an appropriate test battery requires careful consideration of the evaluator’s objectives, participant age, required materials and the three pillars of fundamental movement skills: locomotor, stabilising and manipulative skills. Future research should refine the concept of MC and ensure that the validity of test batteries is rigorously examined. Additionally, using the same test battery across identical subjects and evaluating ecological validity will enhance the sensitivity and applicability of assessments, facilitating their use for both characterisation and intervention.
Keywords: children; coordination; youth; fundamental movements skills; measurement